Eating with a purpose: development and motivators for consumption of superfood - Phuah, Kit Teng; Khoong, Tai Wai; Abdullah, Siti Intan Nurdiana Wong; Ow, Mun Waei; Wong, Kelly Kai Seng (Malaysian Consumer and Family Economics Association, 2020)
This research aimed to examine an integrated and modified Health Belief Model by encapsulating the factors influencing consumer likelihood to consume superfoods as adjusted to the Malaysian population. It was conducted in Peninsular Malaysia from May 2019 until October 2019 using a sample size of 1,000 individuals obtained via purposive sampling, whereby the data were analysed by using structural equation modelling. The result showed that consumer likelihood to consume superfoods was positively influenced by perceived benefits and perceived susceptibility, while negatively influenced by perceived barrier. The cue to action had a direct influence on perceived susceptibility, perceived seriousness, and perceived benefits. Surprisingly, the cue to action was not too influential on perceived barrier and likelihood to consume superfoods. Nevertheless, the proposed modified Health Belief Model fitted the data better than the original model. This implied that it is important to focus on the cue to action especially in the superfood-buying context as opposed to the original Health Belief Model which neglected the cue to action.